Treatability of hazardous substances in industrial wastewater: case studies for textile manufacturing and leather production sectors - GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.Hazardous substances used and produced by different industrial activities pose a potential risk to the environment and to human health. Different physicochemical and/or biological processes are used in industrial wastewater treatment; these methods, however, may not be effective in removing these substances. This study was carried out to comparatively evaluate the removal of hazardous substances through conventional wastewater treatment processes that are used by major industries in Turkey. A four-season monitoring study was carried out in textile manufacturing and leather production sectors, representing industrial activities in Turkey. Samples were analyzed for 45 priority substances defined by the European Union and 250 specific pollutants listed in the Turkish Regulation on Surface Water Quality. For both wastewaters, where biological treatment was performed after pretreatment, their characteristics showed that organics were almost completely removed. except for dichloromethane (44–51% removals) and dioxin and dioxin-like compounds (64–69% removals). Additionally, different removal ratios (16–97%) were obtained for metals; the poorer removal was observed for B, Ba, Ag, Sb, and Si. The remaining metals (Cu, Pb, Sb, V, Si for textile; Cr, Cu, Sb, Si for leather effluents) in the treated wastewaters were still higher than environmental quality standards (EQS) of receiving water bodies. The study revealed that existing treatment processes were not adequate for efficient hazardous substance removal and there is an urgent need to improve them. Finally, advanced treatment technologies were suggested for specific pollutants together with their unit treatment costs.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Aquatic Science; Nature and Landscape Conservation; Environmental Science (miscellaneous); Physical Sciences; Life Sciences; Conventional treatment processes; Hazardous substances; Leather production; Textile manufacturing; Treatment efficiency; BIOLOGICAL TREATMENT; ORGANIC POLLUTANTS; TREATMENT TECHNOLOGIES; AROMATIC-HYDROCARBONS; ACTIVATED CARBON; TREATMENT-PLANT; REMOVAL; MICROPOLLUTANTS; OZONE; WASTEWATERS; Conventional treatment processes; Hazardous substances; Leather production; Textile manufacturing; Treatment efciency